Bosonic fractional quantum hall states on a finite cylinder - Rosson, P; Lubasch, M; Kiffner, M; Jaksch, D (American Physical Society, 2019)
We investigate the ground-state properties of a bosonic Harper-Hofstadter model with local interactions on a finite cylindrical lattice with filling fraction ν = 1/2. We find that our system supports topologically ordered states by calculating the topological entanglement entropy, and its value is in good agreement with the theoretical value for the ν = 1/2 Laughlin state. By exploring the behavior of the density profiles, edge currents, and singleparticle correlation functions, we find that the ground state on the cylinder shows all signatures of a fractional quantum Hall state even for large values of the magnetic flux density. Furthermore, we determine the dependence of the correlation functions and edge currents on the interaction strength. We find that depending on the magnetic flux density, the transition toward Laughlin-like behavior can be either smooth or it can happen abruptly for some critical interaction strength